Legal Dialectics: A Study of Legal Philosophy Legal Theory and Legal Dogmatics in Indonesian Legal Thought: Dialektika Hukum: Kajian Filsafat Hukum Teori Hukum dan Dogmatika Hukum dalam Pemikiran Hukum Indonesia - Irawansah, Didik; Ridwan; Kasmar; Amin, Muhammad (Universitas Muhammadiyah Bima, 2024)
The results of this study show: (1) The dialectic between philosophy, theory, and legal dogmatics influences the development of modern legal thought by creating a legal system that is not only oriented towards legal certainty but also responsive to social justice and the dynamics of society. Legal philosophy provides a moral foundation and values ​​of justice, while legal theory offers a conceptual framework for understanding the function of law in society. Legal dogmatics, as the application of legal rules, ensures that these normative principles can be implemented effectively. The implication is that modern law becomes more adaptive and able to respond to the demands of ever-growing social change, creating a balance between legal certainty and substantive justice. (2) Legal philosophy plays a role in forming principles of justice and morality that form the basis for a just legal system. These principles are then integrated through legal theory, which explains how law should function conceptually, and legal dogmatics, which applies these principles in practice. The interaction between legal philosophy, theory, and dogmatics creates a more balanced legal system, where law is not only applied technically but also considers moral values ​​and justice, so that the legal system becomes fair, effective, and relevant to society.